EDUKASI PENGETAHUAN TENTANG PROPER BODY MECHANICS UNTUK MENGURANGI NYERI LOW BACK PAIN (LBP) PADAKOMUNITAS PERSIT KARTIKA CHANDRA KIRANA KORAMIL JEBRES - Syarifah Syarifah; Sulistiyani Prabu Aji; Noviyati Rahardjo Putri (Health Care : Journal of Community Service, 2025)
Lower back pain (Low Back Pain or LBP) is one of the most common musculoskeletal complaints experienced by women, especially those involved in household activities or caring for toddlers. Activities such as bending, lifting loads, or non-ergonomic breastfeeding positions are major risk factors. Based on this, education about "Proper Body Mechanics" becomes essential to prevent and reduce LBP. The goal is to increase the knowledge of mother members of the Persit Kartika Chandra Kirana in Koramil Jebres regarding correct posture and techniques in daily activities, measure the effectiveness of education through pre-test and post-test methods, and provide practical skills so that they can reduce or prevent LBP complaints. The community service method involves educating women with lower back pain (LBP) about proper body mechanics, which can be conducted in several stages. Educational activities on proper body mechanics have been proven effective in increasing the knowledge and awareness of the wives of Persit Koramil Jebres regarding the prevention and reduction of LBP from 53% to 77%.